Um olhar sobre o cuidado em saúde à população em situação de rua na atenção básica - Ramalho, Dayse Catão (2020)
The increase in the homeless population is increasing worldwide and mainly in the Brazilian territory. In this sense, the inclusion of public policies that reduces the risk that this population group involves, especially in the context of public health care policies, is necessary. The strengthening of strategies that expand and favor access and care for this population, especially in aspects related to ways of living on the street and demand favorable local situations to face the difficulties faced by those on the street. This research aimed to analyze the access of the homeless population to Primary Care services in the city of João Pessoa - PB, from the perspective of professionals from the teams of CnaR teams who work in five health districts in the city. In this sense, research on the challenges faced by this population, without health care as a whole and a guarantee of rights. The aim of this study is to demystify practices and practices allowed in the biomedical, moralistic, prejudiced and fragmented model, to allow a new meaning in the care processes for the individual, to test and expand rights, based on the Psychiatric reform and the Harm reduction policy. The methodology used was qualitative, with semi-structured interviews with nine professionals from the consultancy sector on the street. The analysis was carried out using the content analysis technique proposed by Bardin, in the thematic mode. As contributions obtained through the data obtained and with the development of research aimed at improving and expanding care for people living on the street in Primary Care. These served as a basis for a discussion about difficulties faced by the homeless population, which concerns access to services in Primary Health Care and the realization of their rights as citizens, as well as the challenges faced by professionals from consultants on the streets to effectiveness and guarantee of these rights in the daily life of health services scenarios.